Analysis of Health Risks and Conditions Associated with Smoke Inhalation in Wildfires - Bustos, Edison Huertas; Núñez, Jaime Alfredo Sánchez; Pardo, Lisbeth Carolina Piñeros (Celebes Nursing Journal, 2025)
Introduction: Human health is increasingly threatened by environmental factors such as wildfires, which have risen globally and in Colombia. Wildfire smoke, rich in fine particulate matter, can trigger respiratory and systemic diseases, especially among vulnerable groups. In Girardot, Cundinamarca, limited awareness and prevention efforts highlight the need to assess the health risks of smoke exposure for targeted interventions. Objectives: This research specifically studies the impact of exposure to wildfire smoke on respiratory health in the population of the municipality of Girardot, Cundinamarca, between 2013 and 2023. The main objective is to determine the level of risk and health conditions associated with wildfire smoke exposure in the participating population. Methods: The methodology consisted of surveys administered to 104 participants, who were selected through random sampling. Participants provided sociodemographic information, information on their exposure to wildfire smoke, and information on the presence of respiratory symptoms. Data analysis employed descriptive and inferential statistical techniques, including chi-square and odds ratio (OR) tests with 95% confidence intervals. Microsoft Excel and R, version 4.4.1, were used for statistical data analysis. Results: The results reveal that nighttime exposure to wildfire smoke is associated with the onset of respiratory symptoms. Likewise, it was identified that workplace smoke exposure is also linked to the presence of respiratory symptoms. Conclusion: Therefore, the importance of adopting and implementing preventive, educational, and biosafety measures to mitigate and protect the health of the population in the event of future wildfires is highlighted. The negative effects of wildfire smoke inhalation on health are highlighted.